2023
DOI: 10.1029/2022jg007291
|View full text |Cite
|
Sign up to set email alerts
|

Basin‐Scale CO2 Emissions From the East River in South China: Importance of Small Rivers, Human Impacts and Monsoons

Abstract: River networks are key members in the regional and global carbon (C) cycle (Battin et al., 2009;Cole et al., 2007;Drake et al., 2018). Large quantities of C stabilized by the terrestrial ecosystems are transported from the land to rivers through runoff and groundwater, (Regnier et al., 2022), and this land-river C transport could offset terrestrial C gain and diminish the C sequestration capacity of terrestrial ecosystems (Chi et al., 2020;Duvert et al., 2020;Lauerwald et al., 2020). Emission in the form of ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 77 publications
(144 reference statements)
2
6
0
Order By: Relevance
“…A similar instantaneous response was also observed by Liu et al. (2023) when examining the effects of floods on CO 2 fluxes in an intermittent stream in Inner Mongolia, China. The CO 2 fluxes immediately after rewetting increased by 27‐fold relative to that before the onset of the floods (Liu et al., 2023).…”
Section: Current Research Gaps and Challengessupporting
confidence: 85%
See 4 more Smart Citations
“…A similar instantaneous response was also observed by Liu et al. (2023) when examining the effects of floods on CO 2 fluxes in an intermittent stream in Inner Mongolia, China. The CO 2 fluxes immediately after rewetting increased by 27‐fold relative to that before the onset of the floods (Liu et al., 2023).…”
Section: Current Research Gaps and Challengessupporting
confidence: 85%
“…In incubation experiments with sediments from more than 200 dry IRES worldwide, von Schiller et al ( 2019) found a 32-to 66-fold increase in the respiration rate after sediment rewetting, with an average CO 2 emission rate of 833 mmol m 2 d 1 . A similar instantaneous response was also observed by Liu et al (2023) when examining the effects of floods on CO 2 fluxes in an intermittent stream in Inner Mongolia, China. The CO 2 fluxes immediately after rewetting increased by 27-fold relative to that before the onset of the floods (Liu et al, 2023).…”
Section: Disproportionate Contribution Of Headwater Streamssupporting
confidence: 77%
See 3 more Smart Citations